Tariff harmonization, government revenue and economic integration within ECOWAS : some reflections. - Ariyo, Ademola (1992)
Argues that tariff harmonization has potential significant negative effect on the fiscal operations of ECOWAS. Discusses the prospects for recouping the estimated revenue loss, and offers some suggestions aimed at enhancing the meaningful development of ECOWAS.